Exploring the predictor of teaching quality using the job demands-resources model - M. A. Rafsanjani; A. F. Prakoso; H. D. Wahyudi; S. M. Samin; А. Е. Prabowo; S. A. Wijaya (Russian State Vocational Pedagogical University, 2023)
Introduction. Maintaining teaching quality in higher education in Indonesia is challenging due to the significant job demands placed on lecturers, who are expected to fulfill multiple roles as educators, researchers, and mentors.Aim. The present research aimed to explore the potential of using the job demands-resources (JD-R) model to evaluate the quality of teaching in higher education.Methodology and research methods. This study employs structural equation modelling (SEM) using SmartPLS 3.0 software to analyse the research model based on a random sample of 285 lecturers from nineteen universities in Indonesia.Results. It has been established that role conflict among lecturers negatively impacts teaching quality, whereas self-efficacy positively influences it. The paper presents methods for utilising the JD-R model to examine factors related to the performance of higher education teachers.Scientific novelty. This study, utilising the capabilities of the JD-R model, identifies factors that influence teaching quality and presents mechanisms that underlie the relationship between role conflict and the level of self-efficacy in teaching performance among high school educators in Indonesia.Practical significance. The paper out-lines the opportunities available to university administrations and the Indonesian Ministry of Education, Culture, Research, and Technology for making critical management decisions related to teaching quality. This includes restructuring the educational process to reduce the burden on teachers and expanding the methods used to assess their performance. These goals can be accomplished through the development of innovative organisational support systems.